Selitev mrtvih ptic prek Slovenije - Šere, Dare (Acrocephalus, 1997)
On December 4 th 1996, 3,914 dead Birds were discovered by Slovene customs officers in a specially reconstructed van with Italian numberplates on the Slovene-Hungarian border at Dolga vas near Lendava (Table 1). The Italian driver stated that the birds were from Romania and that he had been given 300 DEM for the transportation of these "goods". He had his van confiscated and was ordered to pay 1500 DEM for committed customs offence ...
Keywords: hunting; lov; ornitologija; otnihology; ptice; tihotapljenje